Growth Kinetic Study of Blue-green Microalgae Arthrospira platensis Using Buffalo Manure as Alternative Media - BRIAN SINAGA; Lianty Simangunsong; Andy Trirakhmadi; Monita Pasaribu; Merry Martgrita (Indonesian Society for microbiology, 2020)
North Sumatera is one of the provinces in Indonesia with the highest buffalo population, which is responsible for the high accumulation of buffalo manure that can cause environmental and aesthetic problems if left untreated. One of the possible alternatives for solving this issue is by implementing buffalo manure as growth media for microorganisms, e.g. microalgae. In this research, buffalo manure was used as alternative media for Arthospira platensis cultivation. Buffalo manure was taken from Sitoluama village, Laguboti, Toba Regency of North Sumatra Province. Research steps included media and culture preparation, cultivation, sampling, sample analysis and verification of constructed models and validation. Buffalo manure concentration in media is varied from 1 g.L-1 to 8 g.L-1 which is analogous to nitrogen content of 0.002 mg.L-1 to 0.018 mg.L-1. Growth data was used for growth kinetic modelling, which was most satisfactory for Monod model (Âµmax = 0.5915 day-1, Ks = 0.421 g.L-1). Â